CONTINUITY OF CARE IN NY. F WITH MODERATE ANEMIA PREGNANCY INDEPENDENT PRACTICE MIDWIFE J. MANURUNG PERAK HAMPARAN DISTRICT KABUPATEN DELI SERDANG YEAR 2025 - Alfrina Rumapea; Rosmani Sinaga; Marliani; Lidia Widarni Hia; Kasihati Buulolo; Rifka Dayanti; Hariati Elina Purba, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
The problem in the case study is how to provide Midwifery Care to Mrs. F who experiences anemia in her pregnancy comprehensively, including Midwifery Care for pregnancy, childbirth, postpartum and family planning at PMB J. Manurung in 2025?. Implementing continuous obstetric care starting from pregnancy, childbirth, newborn, postpartum and family planning. From the results of research on sustainable care that has been given to Mrs. F starting from the third trimester, childbirth, postpartum and breastfeeding, newborns, to family planning which aims to improve the quality of midwifery services. After evaluation, data analysis according to the author's assumption Mrs. F With a pregnancy history of G3P2A0 with a gestational age of 28 weeks 2 days, the results were found from the examination that the fetus in the uterus (intrauterine), single, alive, the back is on the right side of the mother's abdomen, the presentation of the head, not yet in PAP, the condition of the mother and jani is in good condition. At the time of the study on Mrs. F, the author will conduct a comparison or suitability of research on the theory of obstetric management care in pregnant women, childbirth, postpartum childbirth, BBL, and family planning services and will be concluded on the results of the research that has been carried out.